Phenylethyl isothiocyanate mitigates drug-induced liver injury in mice by inhibiting hepatocyte pyroptosis through the NLRP3-caspase-1-GSDMD pathway - An, Ning; Wang, Xiaoru; Qin, Jia; Cheng, Meng; Bai, Mei; Cheng, Jingcai; Xu, Qiang; Wu, Xuefeng (Frontiers in Pharmacology, 2025)
Introduction: Drug-induced liver injury (DILI) represents a distinct form of hepatic damage resulting from exposure to pharmacological agents. The pathological mechanisms underlying DILI are multifaceted and remain incompletely elucidated. However, emerging evidence suggests that cell pyroptosis, a form of programmed cell death associated with inflammation, may serve as a common mechanistic pathway in DILI pathogenesis.Methods: To investigate the role of pyroptosis in DILI, we established a murine model of DILI using triptolide and evaluated the therapeutic potential of phenethyl isothiocyanate (PEITC), a naturally occurring compound, in mitigating liver injury through the modulation of hepatocyte pyroptosis. Mice were administered PEITC at doses ranging from 5 to 20 mg/kg. Cytokine expression was measured using quantitative polymerase chain reaction or biochemical indicator analyzer. Cell signalings were assayed by western blot and immunohistochemistry. The AML12 hepacytes were cultured to investigate the in vitro effects.Results: PEITC treatment markedly attenuated hepatic tissue damage, restored normal liver architecture, and significantly reduced serum levels of transaminases (AST and ALT), while normalizing hepatic metabolic function. These protective effects were mechanistically linked to the suppression of hepatocyte pyroptosis, as PEITC effectively reversed the upregulation of the NLRP3 inflammasome, Caspase-1 cleavage, and Gasdermin D (GSDMD) in triptolide-exposed livers. In vitro studies using cultured hepatocytes further demonstrated that PEITC inhibited the expression and activation of NLRP3, Caspase-1, GSDMD, and other key proteins involved in the pyroptosis pathway. Ultrastructural analysis via electron microscopy corroborated these findings, revealing that PEITC prevented pyroptosis-induced membrane pore formation in hepatocytes.Conclusions: PEITC exerts hepatoprotective effects against DILI by targeting the pyroptosis pathway, thereby highlighting its potential as a novel therapeutic strategy for liver injuries. Our results further implicate cell pyroptosis as a novel target for the attenuation of DILI.